2014
DOI: 10.1128/aem.00294-14
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Microbial Diversity Patterns with Geochemistry in an Extreme and Heterogeneous Environment of Mine Tailings

Abstract: Recent molecular surveys have advanced our understanding of the forces shaping the large-scale ecological distribution of microbes in Earth's extreme habitats, such as hot springs and acid mine drainage. However, few investigations have attempted dense spatial analyses of specific sites to resolve the local diversity of these extraordinary organisms and how communities are shaped by the harsh environmental conditions found there. We have applied a 16S rRNA gene-targeted 454 pyrosequencing approach to explore t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
96
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(109 citation statements)
references
References 86 publications
11
96
2
Order By: Relevance
“…The overall alpha-diversity of the microbial community was widely observed to significantly relate to the acidification process. Liu et al investigated the microbial communities in filed mine tailings at different acidification stages (pH range 2.0-7.0) and described a strong correlation between the pH and the diversity of microbes including the number of phylotypes and phylogenetic diversity (PD) [25]. This gradual decrease of microbial diversity during the acidification of mine tailings was also found in other studies of natural AMD environments [29,48,54], possibly owing to the stronger selective pressure on microorganisms.…”
Section: Microbial Community Function and Dynamics During Amd Generationmentioning
confidence: 79%
See 3 more Smart Citations
“…The overall alpha-diversity of the microbial community was widely observed to significantly relate to the acidification process. Liu et al investigated the microbial communities in filed mine tailings at different acidification stages (pH range 2.0-7.0) and described a strong correlation between the pH and the diversity of microbes including the number of phylotypes and phylogenetic diversity (PD) [25]. This gradual decrease of microbial diversity during the acidification of mine tailings was also found in other studies of natural AMD environments [29,48,54], possibly owing to the stronger selective pressure on microorganisms.…”
Section: Microbial Community Function and Dynamics During Amd Generationmentioning
confidence: 79%
“…For example, according to the result of a simulated experiment of oxidative dissolution of pyrite, the most dominant genera were Tumebacillus, Alicyclobacillus, and Ferroplasma at the early, mid, and final stage, respectively [47]. A detailed microbial community investigation in a natural AMD-generating environment indicated that the key species involved in different acidification stages varied greatly, and the relative abundances of most dominant lineages were significantly correlated with acidity [25]. In many studies, archaea (mostly Ferroplasma spp.)…”
Section: Microbial Community Function and Dynamics During Amd Generationmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, DNA-characterization-based highthroughput methodologies, such as sequencing and subsequent sequence alignment, can directly detect microbial community composition and variations in species with low richness (Shi et al, 2014;Zhao et al, 2014). These methodologies have also been widely adopted to assess the genetic structure and diversity of microbial communities in various environments (Quince et al, 2009;Golebiewski et al, 2014;Liu et al, 2014;Portune et al, 2014;Ren et al, 2014;Singh et al, 2014;Thomson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%